Horseshoe drag in three-dimensional globally isothermal disks - Masset, F. S. (2016)
We study the horseshoe dynamics of a low-mass planet in a three-dimensional, globally isothermal, inviscid disk. We find, as reported in previous work, that the boundaries of the horseshoe region (separatrix sheets) have cylindrical symmetry about the disk´s rotation axis. We interpret this feature as arising from the fact that the whole separatrix sheets have a unique value of Bernoulli´s constant, and that this constant does not depend on altitude, but only on the cylindrical radius, in barotropic disks. We next derive an expression for the torque exerted by the horseshoe region on the planet, or horseshoe drag. Potential vorticity is not materially conserved as in two-dimensional flows, but it obeys a slightly more general conservation law (Ertel´s theorem) that allows an expression for the horseshoe drag identical to the expression in a two-dimensional disk to be obtained. Our results are illustrated and validated by three-dimensional numerical simulations. The horseshoe region is found to be slightly narrower than previously extrapolated from two-dimensional analyses with a suitable softening length of the potential. We discuss the implications of our results for the saturation of the corotation torque, and the possible connection to the flow at the Bondi scale, which the present analysis does not resolve.